Geographical origin of cereal grains based on element analyser-stable isotope ratio mass spectrometry (EA-SIRMS). (1st May 2015) - Wu, Yuluan; Luo, Donghui; Dong, Hao; Wan, Juan; Luo, Haiying; Xian, Yanping; Guo, Xindong; Qin, Fangfang; Han, Wanqing; Wang, Li; Wang, Bin
Highlights: 5 kinds of cereal grains were collected and their isotopic compositions were analysed. Isotopic compositions of abundant rice and wheat samples were detected using IRMS. δ 13 C would be potentially useful for rapid discrimination of geographical origin of cereal grains. Abstract: The stable carbon and nitrogen isotopic compositions ( δ 13 C and δ 13 N) of different cereal grains from different regions were determined, using element analyser-stable isotope ratio mass spectrometry (EA-SIRMS) as the key method. Systematically, δ 13 C and δ 13 N of 5 kinds of cereal grains of different origins, 30 wheat samples from different cultivation areas and 160 rice samples of different cultivars from Guangdong province of China were examined. The results indicated that the δ 13 C values of rice, soybean, millet, wheat and corn were significantly ( P  < 0.05) different within different origins (Heilongjiang, Shandong and Jiangsu province of China), respectively, while δ 13 N values were not. Interestingly, there exists discrimination between these 5 kinds of cereals grains, no matter C-3 or C-4 plants. Further study showed that the δ 13 C values of wheat from Australia, the USA, Canada, and Jiangsu and Shandong province of China were also significantly ( P  < 0.01) different. Furthermore, the P -value test for 160 rice samples of 5 cultivars was not significant ( P  > 0.05), which indicated that the cultivar of cereal grains was not significant based on δ 13 C value. Thus, the comparison of δ 13 C would be potentially useful for rapid and routine discrimination of geographical origin of cereal grains.